The role of behavioural factors and opportunity costs in farmers' participation in voluntary agri-environmental schemes: A systematic review - Schaub, Sergei; Ghazoul, Jaboury; Huber, Robert; Zhang, Wei; Sander, Adelaide; Rees, Charles; Banerjee, Simanti; Finger, Robert (Wiley, 2023)
Agri-environmental schemes (AESs) are increasingly implemented to promote the adoption of environmentally friendly practices by farmers. We use a systematic review to explore the role of behavioural factors and opportunity costs in farmers' decisions to participate in AESs in Australia, Europe and North America. Behavioural factors influence how farmers value and perceive options, while opportunity costs relate to farmers' forgone utility when choosing to participate in schemes. We synthesise insights from 79 articles and over 700 factors explaining the participation in AESs. We find that a set of behavioural factors seem consistently connected to participation, including agricultural training, advice and having positive attitudes towards AESs. Moreover, several factors related to opportunity costs also have a rather consistent relationship with AES participation, including market conditions, implementation efforts, profitability, and management and contract flexibility. However, many relationships of behavioural factors and opportunity costs with AES participation are not as consistent and generalizable as sometimes portrayed and require context-specific interpretation. Those factors with mixed results can still provide insights into farmers' participation decisions as several of them are either ‘positively and insignificantly’ or ‘negatively and insignificantly’ related to participation, such as environmental attitude, trust and farm size. These results suggest that their relationship with AES participation depends on other factors or the setting, highlighting interactions and raising important new research questions. Overall, our results provide several entry points for both researchers and policy-makers, highlighting uncertainties in relationships between factors and participation that should be considered when designing policies.